Model of Leadership Style to Achieve Success of High Private Education Information System - Anwar, Muhammad Tajuddin (International Review of Management and Marketing, 2018)
The purpose of this research is to explain about the influence of employee maturity to situational leadership and also of the success of information systems of private universities Private College Coordinator of area VII and VIII (Kopertis) of region VII and VIII located in East Java and West Nusa Tenggara (NTB) provinces. Sampling was done by purposive sampling, with a sample of 5 high schools. Respondent is the leader who handles SI-PTS at Lower Management level, so that it amounts to 30 leaders in three sub-fields of SI-PTS, namely academic sub-division, financial sub-sector and library sub-sector. The results showed that of the four most significant leadership style is the task maturity and Psychological Maturity and Behavior Participation with determination R of 0.62774 on the success of SI-PTS compared with others. While the influence of task maturity and psychological maturity to the success of SI-PTS showed a significant level with a determination R of 36.44%. The influence of task maturity and psychological maturity to the same success that is with the same value of the variable ability and the willingness variable that is equal to 0.313757. Keywords: Situational Leadership, Systems, Information, Private Higher Education. JEL Classifications: D83, I23 DOI: https://doi.org/10.32479/irmm.7053